Social determinants of participant recruitment and retention in a prospective cohort study of pediatric mild traumatic brain injury - Wells, Jordee M.; Galarneau, Jean-Michel; Minich, Nori M.; Cohen, Daniel M.; Clinton, Kameron; Taylor, H. Gerry; Bigler, Erin D.; Bacevice, Ann; Mihalov, Leslie K.; Bangert, Barbara A.; Zumberge, Nicholas A.; Yeates, Keith Owen (Frontiers in Neurology, 2022)
Background: Prior studies have shown poor recruitment and retention of minoritized groups in clinical trials. Objective: To examine several social determinants as predictors of consent to participate and retention as part of a prospective, longitudinal cohort study of children 8-16 with either mild traumatic brain injury (mild TBI) or orthopedic injury (OI). Methods: Children and families were recruited during acute visits to emergency departments (ED) in two large children’s hospitals in the midwestern United States for a prospective, longitudinal cohort study of children 8-16 with either mild TBI or OI. Results: A total of 588 (mild TBI = 307; OI = 281) eligible children were approached in the ED and 315 (mild TBI = 195; OI = 120) were consented. Children who consented did not differ significantly from those who did not consent in sex or age. Consent rates were higher among Black (60.9%) and multi-racial (76.3%) children than white (45.3%) children. Among the 315 children who consented, 217 returned for a post-acute assessment (mild TBI = 143; OI = 74), a retention rate of 68.9%. Participants who were multi-racial (96.6%) or white (79.8%) were more likely to return for the post-acute visit than those who were Black (54.3%). Conclusions: Racial differences exist in both recruitment and retention of participants in a prospective, longitudinal cohort of children with mild TBI or OI. Further work is needed to understand these differences to ensure equitable participation of minoritized groups in brain injury research.